PENGARUH LOYALITAS KERJA DAN PELATIHAN KERJA TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA SIAK KOTA PEKANBARU - Aidil Syaputra; Rendra Wasnury; Rovanita Rama (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Local water company Tirta Siak Pekanbaru, which is a company belonging to the area is required to improve the working produtivitas employees are encouraged, so as to contribute to increased revenue. This study aims to look at the effect of job loyalty and job training to increase productivity of employees at the local water company Tirta Siak Pekanbaru city. The population in this study were all employees of the company with a total sample of 53 people. Analysis of data using multiple linear regression analysis using SPSS. Results of the study found that loyalty employment and job training partially and simultaneously have a significant influence on employee productivity local water company Tirta Siak Pekanbaru. The amount of influence loyalty employment and vocational training on employee productivity amounted to 59.6%. Results of research conducted by Analytical methods Hirarcy Procces the variable-job training, showed that among the indicators of job training that have the greatest relationship to improve employee productivity. Education and training not only gain knowledge, but also improve work skills, thereby increasing productivity. Based on the research results show that vocational training has a very strong influence on employee productivity. Meaning that job training is a very important variable for the organization.Keywords: Loyalty Employment, Vocational Training and Labor Productivity.